Crosslinking of addition copolymers from tricyclononenes bearing (CH3)3Si‐ and (C2H5O)3Si‐groups as a modification of membrane gas separation materials. Issue 12 (14th May 2019) - Alentiev, Dmitry A.; Egorova, Elena S.; Bermeshev, Maxim V.; Starannikova, Ludmila E.; Yampolskii, Yuri P.; Finkelshtein, Eugene Sh.
Abstract : Here, we report the synthesis and the study of gas‐transport properties of crosslinked highly permeable copolymers from Si‐containing norbornene derivatives. The initial high‐molecular‐weight copolymers were prepared via addition copolymerization of 3‐trimethylsilyltricyclo[4.2.1.0 2, 5 ]non‐7‐ene (TCNSi1) with 3‐triethoxysilyltricyclo[4.2.1.0 2, 5 ]non‐7‐ene (TCNSiOEt) in good or high yields using a Pd‐catalyst. The obtained copolymers included up to 10 mol% of TCNSiOEt units bearing reactive Si–O–C‐containing substituents. The crosslinking was readily realized by using simple sol–gel chemistry in the presence of Sn‐catalyst. The formed crosslinked copolymers were insoluble in common organic solvents. Permeability coefficients of various gases (He, H2, O2, N2, CO2, CH4, C2 H6, C3 H8, n ‐C4 H10 ) in these copolymers before and after crosslinking were determined and the influence of the incorporated TCNSiOEt units as well as the crosslinking on gas transport properties were established. As a result, it was found that only a small reduction of gas‐permeability was observed when TNCSiOEt units were incorporated into the main chains, and the copolymers were crosslinked. At the same time, the selectivity for C4 H10 /CH4 pair was increased. The suggested approach has allowed obtaining crosslinked polymers from Si‐containing monomers without a loss of the main membrane characteristics. POLYM. ENG. SCI., 59:2502–2507, 2019. © 2019 Society of Plastics Engineers